2005
DOI: 10.1007/s00262-005-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumour-associated N-glycolylated variant of GM3 ganglioside in cancer progression: effect over CD4 expression on T cells

Abstract: Gangliosides have diverse biological functions including modulation of immune system response. These molecules are differentially expressed on malignant cells compared with the corresponding normal ones and are involved in cancer progression affecting, in different ways, the host's anti-tumour specific immune responses. Although in humans the N-glycolylated variant of GM3 ganglioside is almost exclusively expressed in tumour tissues, the significance of this glycolipid for malignant cell biology remains obscur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Mouse B16 melanoma cells loaded with Neu5Gc-GM3 showed more lung metastases and increased tumor burden in subcutaneous implants [50]. Moreover, on the contrary of Neu5Ac-GM3, Neu5Gc-GM3 did not inhibit EGF-induced EGFR phosphorylation in A431 cells [51] and down-modulated CD4 molecule in T lymphocytes [52] and dendritic cell differentiation [53]. To further confirm the involvement of GM3 and Neu5Gc-GM3 in melanoma aggressiveness, we demonstrated that a clone isolated from a single melanoma cell line and endowed with higher adhesive and invasive potential, showed a ganglioside pattern composed only by GM3, mainly in the form of Neu5Gc-GM3.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse B16 melanoma cells loaded with Neu5Gc-GM3 showed more lung metastases and increased tumor burden in subcutaneous implants [50]. Moreover, on the contrary of Neu5Ac-GM3, Neu5Gc-GM3 did not inhibit EGF-induced EGFR phosphorylation in A431 cells [51] and down-modulated CD4 molecule in T lymphocytes [52] and dendritic cell differentiation [53]. To further confirm the involvement of GM3 and Neu5Gc-GM3 in melanoma aggressiveness, we demonstrated that a clone isolated from a single melanoma cell line and endowed with higher adhesive and invasive potential, showed a ganglioside pattern composed only by GM3, mainly in the form of Neu5Gc-GM3.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 N-glycolyl (NGc) gangliosides, and particularly NGcGM3, have received attention as a privileged target for cancer therapy. 9 NGcGM3 contributes to cancer progression, not only by influencing dendritic cell differentiation and maturation, but also down-modulating the CD4 expression in T cells 10 and impairing CD4 + CD25 -T lymphocyte functions. 11 Many clinical trials have been performed with a NGcGM3-containing vaccine for the immunotherapy of melanoma [12][13][14][15] and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to changes in the presentation of Neu5Ac, tumour cells also accumulate large amounts of the non-human Neu5Gc that originates from digested food [7,34]. Additionally, an immunomodulatory effect for Neu5Gc has been demonstrated because the ganglioside Neu5GcGM3 induces CD4 down-modulation on T cells [74]. As was previously suggested, antiNeu5Gc antibodies that are present in the circulation of patients can generate only a weak immune response that enhances leukocyte infiltration and angiogenesis, thus stimulating tumour growth.…”
Section: Sialylation α-13-galactosylation and Cancermentioning
confidence: 75%